Mucocele apendicular benigno: manejo quirúrgico seguro. Reporte de un caso y revisión de la literatura - villafaña girón, yanet; Pérez-Sardiña, Yoinel; Hidalgo-Ruiz, Lilianny María; Arias-Manganelly, Julio Michel (Revista de Ciencias Médicas de Pinar del Río, 2025)
Introduction: appendiceal mucocele is a rare entity, present in 0,2–0,7 % of appendectomies, and frequently mimics acute appendicitis. Objective: to present a case of appendiceal mucocele with initial ultrasound diagnosis. Case Presentation: a 53-year-old male patient presented with 72 hours of right iliac fossa pain, leukocytosis (14,500/µL), and abdominal ultrasound revealing a non-compressible cystic structure adjacent to the cecum. Exploratory laparotomy identified a dilated appendix with mucinous content, without signs of malignancy. Conventional appendectomy was performed, and histopathology confirmed a benign appendiceal mucocele (mucinous adenoma, CK20+). This case highlights the usefulness of ultrasound as a first-line diagnostic tool in resource-limited settings, showing 85 % sensitivity; the safety of open surgical approach; and the need for annual ultrasound follow-up, given the possibility of recurrence or malignant transformation. Conclusions: appendiceal mucocele requires a high index of suspicion based on atypical clinical and imaging findings. Multidisciplinary correlation among surgeon, radiologist, and pathologist is essential for optimal management.